Is Administratively Coded Comorbidity and Complication Data in Total Joint Arthroplasty Valid? - Bozic, Kevin J. (Springer-Verlag, 2012)
BACKGROUND: Administrative claims data are increasingly being used in public reporting of provider performance and health services research. However, the concordance between administrative claims data and the clinical record in lower extremity total joint arthroplasty (TJA) is unknown. QUESTIONS/PURPOSES: We evaluated the concordance between administrative claims and the clinical record for 13 commonly reported comorbidities and complications in patients undergoing TJA. METHODS: We compared 13 administratively coded comorbidities and complications derived from hospital billing records with clinical documentation from a consecutive series of 1350 primary and revision TJAs performed at three high-volume institutions during 2009. RESULTS: Concordance between administrative claims and the clinical record varied across comorbidities and complications. Concordance between diabetes and postoperative myocardial infarction was reflected by a kappa value > 0.80; chronic lung disease, coronary artery disease, and postoperative venous thromboembolic events by kappa values between 0.60 and 0.79; and for congestive heart failure, obesity, prior myocardial infarction, peripheral arterial disease, bleeding complications, history of venous thromboembolism, prosthetic-related complications, and postoperative renal failure by kappa values between 0.40 and 0.59. All comorbidities and complications had a high degree of specificity (> 92%) but lower sensitivity (29%–100%). CONCLUSIONS: The data suggest administratively coded comorbidities and complications correlate reasonably well with the clinical record. However, the specificity of administrative claims is much higher than the sensitivity, indicating that comorbidities and complications coded in the administrative record were accurate but often incomplete. LEVEL OF EVIDENCE: Level II, prognostic study. See the Guidelines for Authors for a complete description of levels of evidence.